NOTES ON THE ORIGIN OF DOUBLE-ENTRY BOOKEEPNG. - Yamey, Basil S. (The Accounting Review, 1947)
Abstract The fact that the origin of double-entry bookkeeping remains shrouded in mystery does not detract from the merits of the valuable researches into the early history of accounting made by several scholars, as of July 1947. The search provides an interesting pursuit for the historian even if he knows that the spoor will disappear, sooner or later, in a confused tangle of speculation and conjecture, with the scent of red herring always present. The article deals with one of the possible trails to the unknown origin, or rather, a possible trail provides a tenuous central theme about which some observations are presented. It seems as if, before double-entry appeared, accounting records of proprietorships, whether single or multiple, were confined to records of dealings involving the granting or receiving of credit. The records assumed various forms and often the books of account were mere scraps of paper. Sometimes there were entries in diaries or journals, where the settlement of debts was indicated by the effective though untidy method of deletion. Sometimes the entries in the journal were reclassified into accounts, the beginnings of the modern ledger.